The effects of accounting standards on earnings management and value relevance : a case of Malaysian and Nigerian banks - Ugbede, Onalo (2015)
The mandatory adoption of IFRS beginning from January 1st 2005 by European Union listed firms has attracted contradictory but limited results from emerging economies, particularly, banking sector on the potency of its adoption in reducing earnings management and enhancing value relevance of accounting information. This study, therefore, investigates whether the recent Malaysia and Nigeria’s adoption of IFRS reduces earnings management and enhances value relevance of banks accounting information more than Generally Accepted Accounting Principles (GAAP). All Malaysian and Nigerian conventional banks were investigated within the positivist paradigm over seven year’s panel design. This study employed aggregate discretionary accruals, discretionary loan loss provisions, earnings smoothing, earning management patterns, earnings management goals and loan quality models to evaluate earnings management. Particularly, this study proposed adjustments to the Jones model to be able to investigate banks discretionary accruals. Also, price, return and incremental models were used to evaluate value relevance of accounting information. Data were sourced from banks audited financial statements and stock market reports and analysed using EViews. Findings of this study established that IFRS reduced earnings management and enhanced value relevance of accounting information more than GAAP. This study also established that higher loan quality was most guaranteed under the IFRS provisioning. The findings have both theoretical and practical implications. Theoretically, it further strengthened the findings of previous studies on the potency of IFRS to reduce earnings management and enhance value relevance. Practically, there is urgent need to understand that different accounting standards impact differently on accounting quality, and thus, an immense need to continue to examine their respective impacts on financial statement information. This study is one of the limited studies that investigated Malaysia and Nigeria’s IFRS adoption in relation to earnings management and value relevance of banks accounting information. Also, the adjusted Jones model was able to investigate aggregate discretionary accruals of banks. The findings of this study confirmed the superiority of IFRS over GAAP in reducing earnings management and in enhancing vi value relevance of accounting information. Thus, this study recommends that banks globally should adopt IFRS. Finally, in view of the controversies concerning IFRS, earnings management and value relevance of accounting information, this study recommends that a meta-analysis be conducted.